Comparison of Papanicolaou Smear Quality with the Anatomical Spatula and the Cytobrush–Spatula: A Single-Blind Clinical Trial - Rabiu, Kabiru Afolarin (Niger Med J, 2019)
BACKGROUND: The Papanicolaou (Pap) smear is a standard test for cervical cancer screening; however, the most important challenge is high false-negative results due to inadequate sampling using the Ayres spatula. The cytobrush has been used in combination with the Ayres spatula (cytobrush–spatula) in an attempt to improve the quality of smears with additional costs. The aim of this study was to compare the Pap smear quality with the anatomical spatula (with extended tip) and the cytobrush–spatula. MATERIALS AND METHODS: This was a prospective single-bind clinical trial. One hundred and ten sexually active women aged between 22 and 65 years were randomized into groups, each having two smears at the same time: one with a cytobrush–spatula and another with an anatomical spatula. Fifty-five patients were randomized to have the anatomical spatula first to obtain their smears and 55 were randomized to have the cytobrush–spatula first to obtain their smears. Slides were assessed by a pathologist. RESULTS: There was no significant difference in the quality of the smears using the two devices with respect to cellular adequacy (P = 0.3532), absent blood staining (P = 0.7766), presence of endocervical cells (P = 0.3502), and evidence of transformation zone sampling using the Bethesda criteria (0.4028). Kappa analysis shows moderate inter-rater agreement between the two devices by ability to show evidence of transformation zone using British Society for Clinical Cytology and Bethesda criteria. CONCLUSIONS: There was no significant difference in the quality of smears obtained using the two different methods. The anatomical spatula can be used as a single device in conventional cytology in place of the cytobrush–spatula with the aim of improving the quality of smears without necessarily increasing the cost.